P0436REFRACTORY IGA NEPHROPATHY. A MULTICYTOKINE NORMALIZED LEVELS THERAPY FOR T CELLS IMBALANCE. (6th June 2020) - URIOL, MIGUEL; Obrador Mulet, Aina; Tugores, Ana; Daza, Vanessa; Gomez, Ana; Gasco, Joan
Abstract: Background and Aims: Interleukine-17(IL-17) is a pro-inflammatory cytokine which influences in glomerulonephritis (GN) in animal models. IgA nephropathy (IgAN) is a primary GN with auto-inflammatory and autoimmune features. Imbalances in Th1/Th17 and Treg/Th17 have been associated with the pathogenesis of the IgAN. We evaluated the effect of sequential treatment with a selective vitamin D receptor activator and with an IL-17 blocker in patients with refractory IgA GN (r-IgAN). Method: Five patients with r-IgAN (previously treated with steroids, mycophenolate, tacrolimus and a renin-angiotensin-aldosterone system inhibitor) were treated initially with paricalcitol and six months later with secukinumab (IL-17A blocker) with the objective to improve anti-inflammatory and subsequentially inhibit pro-inflammatory milieu, respectively. We evaluate the evolution of the proteinuria, haematuria, plasma creatinine and urinary N-acetyl-beta-D-glucosaminidase: u-NAG, as a measure of lysosomal activity during the first month of treatment (induction phase) and at month 3 after treatment. We also evaluate the evolution of the evolution of the Th1/Th17 and Treg/Th17 ratio in whole blood. We evaluated the changes at month (M) 0, 1 and 3. Results: Five males were included. Age: 43±11 years. Proteinuria (24h-collected) decreased along the study from 3.5, 2.1 to 1.6g (P<0.01) at M0, M1 and M3 respectively. Four (80%) patients who presented haematuria at month 0 disappeared at month 3. Creatinine did not show changes over time (1.84, 1.88 and 1.95 mg/dl for M0, M1 and M3, P=0.44). uNAG increased after induction phase from 7.2 to 9.8(P= 0.01) and finally decreased to 8.3 at month 3(P=1, respect to month1). Uric acid decreased but not significantly from 8.0, 7.1 and 7.6g/dl at any time point. The ratio Th1/Th17 and Treg/TH17 changed from the month 0 to month 3, from 1.8 to 2.6 (P =0.25) and 0.23 to 0.32 (P=0.16), respectively. Conclusion: Sequential treatment was associated with a reduction in proteinuria and haematuria was well controlled. The changes in u-NAG suggest and intensive initial effect on the lysosomal activity since no changes in renal function was observed. The theoretical benefit of the Th1/Th17 and Treg/Th17 ratio represents a new modality of treatment that need to be rigorously evaluated for its clinical implication in r-IgAN patients.